Studies on Neotropical Pseudophyllinae: The status of the genus Brachyauchenus Brunner von Wattenwyl, 1895 and its species (Orthoptera: Tettigoniidae: Pseudophyllinae: Platyphyllini) - Cadena-Castañeda, Oscar J.; Rodríguez, Nixon Oscar Parra; Tavares, Gustavo Costa; Rodríguez, Diana Marcela Trujillo; Arias, Ronald Fernando Quintana (Zootaxa, 2021)
In this contribution to the subfamily Pseudophyllinae in the Neotropics, we focus on reviewing the status of the genus Brachyauchenus and its four included species. After this revision, the genus remains monotypic, including only B. castaneus (type species), so it is necessary to provide a new diagnosis, since the current has characteristics of species that in the past was moved to Triencentrus, in addition to the characteristics of the species that are being excluded here. B. castaneus is redescribed to complement the characteristics of the genus, the unknown female is described, and new distribution data are provided, refuting the presence of this species in Bogotá, Colombia, its type locality. Brachyauchenus festae and B. minutus are grouped into the new genus Mikrischyrum n. gen. (Platyphyllini) which is similar to Baliophyllum and Drepanoxiphus, and a key is provided to differentiate these species. Brachyauchenus varicosus is being moved to the genus Stenoschema (Pleminiini), restricting the distribution of Brachyauchenus to the center and north of the eastern slope of the Colombian Andes and the new genus in Panama and the Peruvian Amazon. A map is included with the distribution data of the species studied here. Finally, the variation of the coloration of some species and the current taxonomic panorama of the tribe Platyphyllini are discussed.